A study of water wave reflection using close range photogrammetry - Petzer, J M (Department of Civil Engineering, 2016)
The intention of this investigation is to investigate the various forms of water wave reflection to a high degree of accuracy. Close range photogrammetry is the technique that is used to measure the water surface profile, as it produces an accurate and comprehensive analysis of the water surface profiles. Conventional photogrammetry techniques (photography) were used in preference to near real time photogrammetry (digital). Although near real time photogrammetry has the advantage of a far higher rate of data acquisition, it does not achieve the same degree of accuracy as can be achieved by conventional photogrammetry, the technique finally used for this investigation. For the generation of the desired wave patterns, certain equipment was developed and modified. To test the various angles of incidence a moveable reflecting wall was built. Due to the small size of the wave basin, an efficient wave absorber was required to absorb the reflected wave generated when oblique wave reflection was investigated. It was observed that a very poor quality wave was being generated by the wave generator, as a result of its flexibility. Consequently the wave generator was stiffened considerably which improved the wave generated. Interesting information was obtained from the analysis of the standing wave. A coefficient of reflection of 1,6 at the reflection wall was obtained, this places new emphasis on the relationship between the standing wave and overtopping. The oblique wave reflection resu1ts corresponded well with theoretical predictions, while no well-defined trends were established for the mach wave. The data for the mace wave did however suggest that previously established trends for the mach wave may not be correct. Close range photogrammetry produced accurate results, and is an excellent method for water surface profile measurement. The results obtained showed that the wave generator was not generating a pure wave, which lead to unknown errors in the results of spot heights. Conventional photogrammetry is a slow process, so not enough data was acquired to adequately analyse the reflection trends. This suggests that in order for the trends to be well-established, near real time photogrammetry should be used once these systems have developed sufficient accuracy.